Perencanaan Strategis dalam Penyelenggaraan Pendidikan di Madrasah - Nahrowi Nahrowi (STAIFAS-Press, 2017)
Implementation of education can not be separated by management, which contains Planning, Organizing, Actuatin and controlling, with the management of both educational institutions able to provide optimal service to the community, with quality management educational institutions capable of printing quality generation and with good quality management also good institutions capable of bringing positive change to this country. Planning as a first step in management has a very important role as a capital management of an institution / institution, which will produce the generations of excellence in achieving, independent, noble and able to compete with other countries. Therefore, the head of the madrasah needs to apply the strategic planning in the madrasah which includes the Foundational Model, the Early Action Planning Model and The Three-Strand Concurrent Model with their respective characteristics becoming part of the strategic management process related to the short, medium and long term objectives identification process from an institution or organization, extracting ideas and options, taking necessary steps to achieve the stated objectives, and monitoring (monitoring) progress or failure in order to determine future strategies.Â Keywords: Perencanaan Strategis dan Penyelenggaraan Pendidikan